Recent Advances on Pt-Based Compounds for Theranostic Applications - Giulia Ferrari; Ines Lopez-Martinez; Thomas Wanek; Claudia Kuntner; Diego Montagner (Molecules, 2024)
Since the discovery of cisplatin’s antitumoral activity and its approval as an anticancer drug, significant efforts have been made to enhance its physiological stability and anticancer efficacy and to reduce its side effects. With the rapid development of targeted and personalized therapies, and the promising theranostic approach, platinum drugs have found new opportunities in more sophisticated systems. Theranostic agents combine diagnostic and therapeutic moieties in one scaffold, enabling simultaneous disease monitoring, therapy delivery, response tracking, and treatment efficacy evaluation. In these systems, the platinum core serves as the therapeutic agent, while the functionalized ligand provides diagnostic tools using various imaging techniques. This review aims to highlight the significant role of platinum–based complexes in theranostic applications, and, to the best of our knowledge, this is the first focused contribution on this type of platinum compounds. This review presents a brief introduction to the development of platinum chemotherapeutic drugs, their limitations, and resistance mechanisms. It then describes recent advancements in integrating platinum complexes with diagnostic agents for both tumor treatment and monitoring. The main body is organized into three categories based on imaging techniques: fluorescence, positron emission tomography (PET), single–photon emission computed tomography (SPECT), and magnetic resonance imaging (MRI). Finally, this review outlines promising strategies and future perspectives in this evolving field.